Teaching, research, extension and management: UNIFAP's contribution to the SDGS of the 2030 agenda - Pinheiro , Nalimilson Gomes; Ferreira, Jose Francisco Carvalho; Freitas, Josimar da Silva; Freitas, Anne Caroline Pinheiro de (Seven Editora, 2023)
This study analyzes the integration of the Sustainable Development Goals (ODS) of the 2030 Agenda in UNIFAP academic practices between 2005 and 2021. The study aims to confront the academic practices of UNIFAP in the period from 2005 to 2021 with the ODS of the 2030 Agenda, aiming to perspective to what extent the institution contributes to the implementation of these objectives in the local context and identify possible impasses that affect its implementation capacity. A descriptive and exploratory approach was used, employing bibliographic and documentary techniques to collect and classify the actions related to the ODS. The list of keywords prepared by the Institute of Applied Economic Research (IPEA) in collaboration with the National Council of Justice (CNJ) was used to classify the actions. The results show that UNIFAP is a strategic apparatus in the promotion of the ODS, focusing its efforts on the challenges presented by ODS 8, 4, 16 and 3, followed by ODS 9, 11, 15 and 10. On the other hand, ODS 17, 14, 12, 2, 5, 13, 6, 7 and 1 receive less attention. It is important to emphasize that the parts of UNIFAP academic system have contact with the ODS in different ways, revealing the disarticulation between their functions and the rupture of the inseparability between teaching, research, extension and management. DOI:https://doi.org/10.56238/alookdevelopv1-099